Cystic thymoma presenting with urticaria: a case report - Gopinath, Manoj; Gulati, Deepika (International Journal of Research in Medical Sciences, 2016)
Thymomas are epithelial neoplasms of the thymus and are the most common primary tumors of the anterior superior mediastinum, although it can also arise in other locations like the neck, the middle or posterior mediastinum, the lung and the pleural cavity. Ectopic thymomas are said to arise from scattered thymic elements as a result of failure of migration into the anterosuperior mediastinum. The neoplasm may be well encapsulated or may display varying degrees of invasion of the tumor capsule and the adjacent structures. We report a case of non-invasive cystic thymoma in a young individual with unusual clinical presentation and imaging findings.